Dampak Covid-19 Terhadap Potensi Pajak Hiburan dan Kontribusi Terhadap Pendapatan Asli Daerah Kota Batu (Studi Kasus Dinas Pendapatan Kota Batu) - Marianus Vianey Dede; Poppy Indrihastuti; Yayuk Sulistyowaty (Jurnal Akuntansi, 2021)
Abstract This study aims to determine the impact of Covid-19 on the potential for entertainment tax and its contribution to the local revenue of Batu City. The research method used is a qualitative method with an interpretive approach. This research takes the object of Batu City Revenue Service. The data sources are primary data and secondary data. This research data collection technique using observation, interview and documentation techniques. this research, the results found can be concluded that, the potential for entertainment tax from year to year plays an important role with the aim of increasing PAD. The contribution of the entertainment local tax to PAD in 2020, in the situation of the Corona-19 Virus, has decreased, and also Entertainment tax revenue from 2018-2020 has not been optimal based on the existing potential Keywords : Covid-19, Entertainment Tax, Contribution, and PAD Kota Batu